A Survey of SignCryption Its Types and Techniques (International Journal of Engineering and Computer Science, 2017)
In today’s internet world where nothing is protect, since the communication by transmitting of sending and receiving digital products over the open network occur very frequently the security of information is very important. Everyday so many techniques are obtaining to make message and image secure with high rate of security. Some of the encryption techniques used selective part of an image for encryption and some others apply encryption algorithm on whole image bit by bit. In this paper the existing works on the visual cryptography encryption techniques has been surveyed. Six visual cryptography encryption techniques are studied and analyzed well to analyze the performance of the encryption and decryption methods and also to ensure high rate of secure communication